“Ajustar à forma do viver cristão”: Missão católica e resistências em terras africanas - Almeida, Carlos (2017)
Christianity is one of the hallmarks of European presence in the cultural space of Central Africa. Since the baptism of the ruler of Mbanza Kongo, in 1491, symbols, rituals, ceremonial practices were incorporated in some societies, to the point that some authors speak of an “African Christianity.” This paper focuses on three guides for missionary action prepared by Capuchins friars who have gone through the region between the last quarter of 17th century and the 18th mid-century. Its analysis allows us to reconstruct the evangelization program in African lands and the anthropological thought that underlies it, but above all to shed light on the dynamism of African societies and the problems and resistance raised to the Catholic proposal.